Poly-ε-Caprolactone Implants for Benznidazole Prolonged Release: An Alternative to Chagas Disease Oral Treatment - Ana Lia Mazzeti; Karolina R. Gonçalves; Patrícia Ferreira Boasquívis; Jamile Barbosa; Bruno G. Pereira; Maria de Nazaré Correia Soeiro; Vanessa Carla Furtado Mosqueira; Maria Terezinha Bahia (MDPI AG, 2023)
Benznidazole (BZ) tablets are the currently prescribed treatment for Chagas disease. However, BZ presents limited efficacy and a prolonged treatment regimen with dose-dependent side effects. The design and development of new BZ subcutaneous (SC) implants based on the biodegradable poly-ɛ-caprolactone (PCL) is proposed in this study for a controlled release of BZ and to improve patient compliance. The BZ-PCL implants were characterized by X-ray diffraction, differential scanning calorimetry, and scanning electron microscopy, which indicated that BZ remains in its crystalline state dispersed in the polymer matrix with no polymorphic transitions. BZ-PCL implants, even at the highest doses, induce no alteration of the levels of hepatic enzymes in treated animals. BZ release from implants to blood was monitored in plasma during and after treatment in healthy and infected animals. Implants at equivalent oral doses increase the body's exposure to BZ in the first days compared with oral therapy, exhibiting a safe profile and allowing sustained BZ concentrations in plasma to induce a cure of all mice in the experimental model of acute infection by the Y strain of T. cruzi. BZ-PCL implants have the same efficacy as 40 daily oral doses of BZ. Biodegradable BZ implants are a promising option to reduce failures related to poor adherence to treatment, with more comfort for patients, and with sustained BZ plasma concentration in the blood. These results are relevant for optimizing human Chagas disease treatment regimens.